Physiological studies on "choking" in judo - Part 1 - Studies in general - Ikai, M.; Yamakawa, J.; Ogawa, S.; Akutsu, K.; Masuda, M.; Matsumoto, Y. (Association for the Scientific Studies on Judo, Kodokan, 1958)
In order to study the effect upon the human body of "choking" in judo, the "Research Group for the Study of Choking in Judo" was formed within the Society for Scientific Research of Judo, Kodokan. "Choking" is a special technique used in judo, and it consists in strangling the neck of the adversary, thereby imparting pain or even making the oponent fall unconscious. Hence, the physiological studies on the effect of "choking" and its resulting unconsciousness is a matter of great import in order to obtain a proper understqnding of judo, and also in the preventive aspect of the dangers accompanying judo. The late Dr. K. Saito and his colleagues have made electroencephalographic studies during "choking", and have reported that changes observed while the subject was in a state of unconsciousness resulting from the "choking", was identical to those observed in a patient during an epileptic seizure. In the present paper we wish to report our further studies on the subject. The following were the main objectives of our studies: 1) The differences in the effect of the various methods of "choking". 2) The duration of the effect of "choking" on the body. 3) The physiological mechanism of the resulting state of unconsciousness. 4) The prevention of the dangers accompanying "choking".